2010
DOI: 10.1002/acp.1715
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cognitive predispositions on exploration decisions in the minerals industry

Abstract: Minerals exploration is conducted within an environment of ambiguity in the information and a high degree of uncertainty concerning success. In an extension and application of Tetlock (2005) the present research examined the impact of cognitive predispositions on the quality of minerals exploration decision-making. Utilising instruments specifically designed to assess thinking and judgement predispositions results indicate that for this sample (n ¼ 94) an enjoyment of rational thinking and the need for cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Wastell et al, 2011), and / or explorers being focused on other projects elsewhere, not turning over ground efficiently or hanging on to ground that is not worth keeping (i.e., "pet project syndrome"), thereby wasting time and investor dollars. A point in case is the fact that most licences (i.e., 262 of 346, or 76%) never progressed from their initial stage, and in most cases this stage was stage B.…”
Section: Historic Explorationmentioning
confidence: 99%
“…Wastell et al, 2011), and / or explorers being focused on other projects elsewhere, not turning over ground efficiently or hanging on to ground that is not worth keeping (i.e., "pet project syndrome"), thereby wasting time and investor dollars. A point in case is the fact that most licences (i.e., 262 of 346, or 76%) never progressed from their initial stage, and in most cases this stage was stage B.…”
Section: Historic Explorationmentioning
confidence: 99%
“…Rankey and Mitchell 2003 found that seismic interpretations are influenced by the interpreter's biases based on previous experience, preconceived notions, types of data available, data quality and geological understanding, whereas Bond et al 2007 claimed that prior knowledge had a greater influence. In a study specifically focusing on mineral exploration, Wastell et al 2011 studied decision uncertainties. They reported that variability in mineral exploration decisionmaking is due to human predispositions such as rational thinking and cognitive closure.…”
Section: Introductionmentioning
confidence: 99%
“…The above mentioned researches demonstrated between-interpreter variability solely on seismic data. On the other hand, Wastell et al (2011) reported that variability in mineral exploration decision-making is due to human predisposition such as rational thinking and cognitive closure. All of the above studies used interpretation outputs and interpreters' feedback to analyse interpreter variability.…”
Section: Introductionmentioning
confidence: 99%